Сross-sectional anatomic study of direct positional relationships between mandibular canal and roots of posterior teeth using cone beam computed tomography. - Sergey Lvovich Kabak; Natallia Victorovna Zhuravleva; Yuliya Michailovna Melnichenko; Nina Alexandrovna Savrasova (Universidad de Concepción., 2018)
Objectives: To establish the frequency of the various types of direct contacts of the root apices with the wall of the mandibular canal and to determine gender differences in number of such contacts in a selected Belarusian population using cone beam computed tomography. Methodology: One hundred and two cone beam computed tomography scans were analyzed to classify the types of contact and three-dimensional relationship between the mandibular teeth and the mandibular canal. Results: The direct contact between the teeth and the mandibular canal was observed in 63.7% of patients. Overall 300 roots of 189 teeth were in direct contact with the mandibular canal: 9.3% were second premolars, 14.7% were first molars, 33.8% were second molars and 50.0% were third molars. There were no statistically significant differences in the number of teeth with direct contact with the mandibular canal between males and females. Conclusion: The direct contact of the root apices with the mandibular canal was most often found in the second and third molars. The root apices of the third molars had the greatest variability of location relatively to the mandibular canal.